The effectiveness of village budget used for Village’s development - Afrizal Tjoetra, Mursyidin, Fiandy Mauliansyah,; Zikri Muhammad, Jumadil Saputra, (Opción, 2019)
Village Budgeting is allocated by the central government to villages in Indonesia as a form of recognition. This research is analyzing the effectiveness of the use of the budget towards the village development in 2018 by considering several indicators as a measurement tool for this research. The results show that (1) village development that is carried out without need is not effective, (2) new developments being used well by the community (3) The indicators of supervision and control are carried out by socializing gampong activity programs and involving all levels of society in the village.